Design and Implementation of Storage of Network Component Based on NetFPGA10G - Shuolin Zhang; Hongbin Luo (Dianxin kexue)
Presently, it is hot to do research about the next generation network architecture based on the content centric network. The network component, as an important part of it, will be able to forward as well as save the content in the meantime inevitably. New type of network component was designed and implemented, based on NetFPGA10G hardware platform, to forward the data and store the content at the same time, thus to improve the utilization rate of network resources.